MICROTEACHING LESSON ON INCREASING THE STUDENT TEACHERS’ ABILITY IN TEACHING ENGLISH - Destri Sihite Sihite; Aswadi Jaya; Asti Veto Mortini (Esteem Journal of English Education Study Programme, 2024)
The goal of this study is to find out what student teachers think about the benefits of the Microteaching Lesson for Teaching Ability at PGRI Palembang University. The study's team of researchers used a qualitative descriptive strategy. There are 30 sixth-semester English education student teachers as the participants. Data collection techniques included observation, interview, questionnair, and documentation. In order to collect data, the researcher interviewed 30 student teachers to learn more about five different issues. She then gave a questionnaire containing 15 statements to 30 student teachers. The findings of the questionnaire showed that students believed that microteaching had a beneficial effect on their capacity to instruct. Based on the results of the interviews, the researcher also came to the conclusion that the narrative presentations of the students demonstrated how their perceptions of the microteaching course affected their teaching strategies. Students think that by taking part in microteaching, they will be able to improve their teaching abilities through lesson preparation, content explanation, time-management, and teaching self-confidence abilities. Keywords: microteaching, student teachers, and English